Pressure prediction in deep-water pipeline considering formation of natural gas hydrate - Mo, Fei; Qi, Zhilin; Huang, Xiaoliang; Li, Qingping; Yan, Wende; Wang, Shuai (Frontiers in Earth Science, 2022)
Pressure in the deep-water pipeline is an important parameter that should be carefully predicted to control the natural gas transport in petroleum industry. However the present methods to predict pressure along the deep-water pipeline are complex and time-consuming. Some methods even ignore the formation of natural gas hydrate leading to the inaccurate pressure prediction. In this work, we proposed a model to predict the pressure along the deep-water pipeline considering the reduction of pipeline radius induced by the formation of natural gas hydrate. The model was validated by experimental data and was applied to the real deep-water pipeline in China. Results indicate that the decline of pressure in the pipeline is mainly caused by the reduction of pipeline radius due to the formation of natural gas hydrate compared with the flow resistance caused by viscous flow. The decline of pressure becomes faster against time with the 40% pressure loss at the fifth year of natural gas transport. This model enables to obtain the pressure values in the deep-water pipeline with high accuracy and good convenience.